14C Contamination Testing in Natural Abundance Laboratories: A New Preparation Method Using Wet Chemical Oxidation and Some Experiences. Issue 4 (24th October 2016) - McIntyre, Cameron P; Lechleitner, Franziska; Lang, Susan Q; Haghiour, Negar; Fahrni, Simon; Wacker, Lukas; Synal, Hans-Arno
Abstract: Substances enriched with radiocarbon can easily contaminate samples and laboratories used for natural abundance measurements. We have developed a new method using wet chemical oxidation for swabbing laboratories and equipment to test for 14 C contamination. Here, we report the findings of 18 months' work and more than 800 tests covering studies at multiple locations. Evidence of past and current use of enriched 14 C was found at all but one location and a program of testing and communication was used to mitigate its effects. Remediation was attempted with mixed success and depended on the complexity and level of the contamination. We describe four cases from different situations.